GUI toolkit development for neuroimaging data preparation - Lim, Gia Lim (Nanyang Technological University, 2022)
The evolution of magnetic resonance imaging (MRI) techniques has allowed many studies to use techniques such as functional MRI (fMRI) for a non-invasive study of the brain. [1] Given the increasing pervasiveness of neurological diseases, more is required in neuroimaging technology and subsequent data analysis. [2]